Association of Clinical Features and Hematological Laboratoriesbetween Ph (+)/BCR-ABL (+) Chronic Myeloid Leukemia and Other Type of Ph/BCR-ABL Chronic Myeloid Leukemia - Rajabto, Wulyo; Harryanto, A.; Tadjoedin, Hilman; Harimurti, Kuntjoro (Jurnal Penyakit Dalam Indonesia, 2018)
Introduction. Patients with chronic phase Chronic Myeloid Leukemia (CML) at Hematology-Medical Oncology Clinic Department of Internal Medicine dr. Cipto Mangunkusumo National Hospital who haveperformed cytogenetic and RTPCR BCR-ABL examination showed: Ph (+)/BCR-ABL (+) CML and other type of Ph/BCR-ABL CML. This study aims to identify the clinical features and hematological laboratories of chronic phase CML, the proportion of Ph (+)/BCR-ABL (+) CML, and association of clinical features and hematological laboratories between Ph (+)/BCR-ABL (+) CML and other type of Ph/ BCR-ABL CML. Methods. This is a cross-sectional study. The samples were taken by consecutive method. We used Chi-square test and logistic regression analysis. Association between variables considered significant when p value <0.05. Results. There were 80 subjects with chronic phase CML. Mean of age was: 39.4 (standard deviation 13.1) years. The comparison of clinical features and hematological laboratories between Ph (+)/BCR-ABL (+) CML and other type of Ph/ 12 | Jurnal Penyakit Dalam Indonesia | Vol. 5, No. 1 | Maret 2018 Wulyo Rajabto, A. Harryanto, Hilman Tadjoedin, Kuntjoro Harimurti BCR-ABL CML were: Symptomatic 80.6% : 100%; splenomegaly 82% : 92.3%; median of Hb 10,3 g/dL : 10,3 g/dL; median of white blood cell 124.620 : 127.050; median of thrombocyte 455.000 : 487.000. Bivariate and multivariate analysis showed no significant association of clinical features and hematological laboratories between Ph (+)/BCR-ABL (+) CML and other type of Ph/BCR-ABL CML. Conclusion. There was no significant association of clinical features and hematological laboratories between Ph (+)/BCRABL (+) CML and other type of Ph/BCR-ABL CML.